2015
DOI: 10.3233/jhd-150158
|View full text |Cite
|
Sign up to set email alerts
|

Huntington’s Disease in Arab Countries

Abstract: Huntington's disease (HD) is an inherited neurodegenerative disorder. Involuntary choreaform movements are the main symptom. The prevalence of HD in Arab countries is not fully understood, as there are only a few reports indicating disease incidence. Therefore, there is an urgent need for an investigation to determine the frequency of HD in the Middle East, especially within Arab countries, and at the same time enhance people's awareness of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The main reasons for exclusion at this stage were the following: conference abstracts (n = 38), outcomes of interest not discussed (n = 9), editorial or book chapters (n = 5), duplicates not filtered through COVIDENCE (n = 5), articles not written in English or French (n = 2), article included in previous review (n = 1), and publication using the same data in another included study (n = 1). Seven review articles were identified 15 , 16 , 17 , 18 , 19 , 20 that were excluded and used to screen the references for citations not captured through the search strategy; one study was identified through this process. 21 The search was rerun in February 2022, identifying an additional 188 abstracts, with five studies meeting our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The main reasons for exclusion at this stage were the following: conference abstracts (n = 38), outcomes of interest not discussed (n = 9), editorial or book chapters (n = 5), duplicates not filtered through COVIDENCE (n = 5), articles not written in English or French (n = 2), article included in previous review (n = 1), and publication using the same data in another included study (n = 1). Seven review articles were identified 15 , 16 , 17 , 18 , 19 , 20 that were excluded and used to screen the references for citations not captured through the search strategy; one study was identified through this process. 21 The search was rerun in February 2022, identifying an additional 188 abstracts, with five studies meeting our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%